Associations Between Peer Victimization and Problematic Internet Use Among Adolescents: Humor Makes a Difference. Issue 13 (July 2023) - Zheng, Xintong; Chen, Jianwen; Yu, Quanlei; Xiong, Qing; Zhang, Lin; Li, Congcong; Shi, Shuping
With the increasing development of science and technology, the Internet has become an essential part of people's daily lives providing great convenience. However, the Internet also leads to problematic Internet use (PIU) among adolescents, which has attracted increasing attention from the academic community. Peer victimization is a pervasive stressor among adolescents and has been proven to lead to a series of mental health challenges. Although the association between peer victimization and PIU has been well documented, the underlying mechanism remains unclear. This study aimed to understand how and when peer victimization increases the risk of PIU among adolescents. Building on Agnew's general strain theory, this study hypothesized that depression mediates the relationship between peer victimization and PIU and humor moderates the mediating model. To examine these hypotheses, 469 middle school students were recruited to complete a series of questionnaires on peer victimization, depression, humor, and PIU. The results showed that depression partially mediated the relationship between peer victimization and PIU. A moderated mediation analysis indicated that humor moderated the indirect pathway, consistent with the reverse stress-buffering model, the relationship between peer victimization and depression was stronger for adolescents with high humor. However, the relationship between depression and PIU was weaker in adolescents with high humor, which is in line with the stress-buffering model. These findings could be of significance in understanding the underlying mechanism of PIU associated with peer victimization and provide a new perspective for preventing PIU among adolescents, especially those experiencing peer victimization. The limitations and considerations for future research are discussed.